Double trouble? Towards an epistemology of co-infection (Medicine Anthropology Theory, 2015)
Tuberculosis and HIV co-infection came to figure as one of the major global health problems at the beginning of the twenty-first century, with multiple attempts to tackle this intricate issue on epidemiological, clinical, and public health levels. In this article, we propose thinking beyond the practical problems caused by co-infections in order to explore medicine’s epistemological attachment to the idea of single diseases, using TB/HIV as an analytical lever. We retrace how TB/HIV co-infection has been problematised in public health discourses since the 1990s, particularly in WHO reports and international public health journals, and show that it has been mainly discussed as a complex biosocial phenomenon in need of more resources. The epistemological interrogation of the concept of co-infection itself – as an entangled object of two or more diseases with different histories and social, political, and scientific identities – is largely missing. To elaborate on this gap, we look at the translational processes between the two diseases and their communities, and suggest concrete historical and ethnographic entry points for future research on this global health phenomenon.